Stability and Adaptability of Triticale (Triticosecale Wittm. ex A. Camus) Varieties Across Environmental Conditions in the Highlands of Southern Ethiopia - Tariku Simion Dojamo; Selamawit Markos Takiso; Melese Lema Tessema (International Journal of Agronomy)
Triticale combines the yield and quality of wheat with the disease resistance of rye. To choose stable and reasonably high-yielding varieties and to estimate the degree of variation and environmental interactions, five triticale varieties and one local check were assessed at Dita, Chencha, Bonke, and Kamba localities during 2020 and 2021 in Gamo, South Ethiopia. Analysis of variance (ANOVA), the additive main effect and multiplicative interaction (AMMI) model, and interaction principal component analysis (IPCA1 and IPCA2) indicated significant (p≤0.01) differences between habitats, varieties, and their interactions. The contributions of IPCAs 1 and 2 to the overall variety by environment interaction were substantial (p≤0.01) and accounted for 67.3% and 18.1%, respectively. The average grain yield of the varieties Sinan (4085 kg·ha−1) and Dersolign (4081 kg·ha−1) performed better than those of the other varieties without significantly varying, and Minet (3614 kg·ha−1) was next. The Models demonstrated that Dersolign and Minet were stable and recommended for production in a variety of environments with IPCA values close to zero, low (GSI), low AMMI stability value, and high mean grain yield throughout the environments. Dersolign and Minet are hence for broad production due to their high inflexibility.